2004
DOI: 10.1016/j.jvs.2004.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Silicone patch saphenoplasty to prevent repeat recurrence after surgery to treat recurrent saphenofemoral incompetence: long-term follow-up study

Abstract: The use of a silicone patch at repeat operation to treat recurrent varicose veins caused by new incompetence at the level of the saphenofemoral junction is associated with a lower incidence of recurrent thigh varicosities and neovascularization compared with a control group in which no additional barrier technique was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 44 publications
0
43
0
5
Order By: Relevance
“…Neovascularization has been implicated as the leading cause of recurrence in several studies 11,28 -31 , with rates as high as 52 per cent at 2 years 11,32 and 79 per cent at 5 years 8,13 ; evidence of neovascularization on duplex imaging at 1 year has shown a positive predictive value for clinical recurrence of 70-100 per cent 33 . This is ultimately linked to the need for reintervention 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Neovascularization has been implicated as the leading cause of recurrence in several studies 11,28 -31 , with rates as high as 52 per cent at 2 years 11,32 and 79 per cent at 5 years 8,13 ; evidence of neovascularization on duplex imaging at 1 year has shown a positive predictive value for clinical recurrence of 70-100 per cent 33 . This is ultimately linked to the need for reintervention 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have reported the efficacy of silicone patch interposition at SFJt in reducing neovascularization, but there is high incidence of deep vein thrombosis with the use of silicone implant [14,18]. Rij et al reported a highly significant decrease in n e o v a s c u l a r r e c u r r e n c e a t t h e S F J w h e n a polytetrafluoroethylene patch (PTFE patch, 3×3 cm) is interposed between the ligated vein stump and the overlying soft tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29] The frequency of inguinal reflux associated with varicose recurrence in our study conforms to reported figures, 2-4,7-11 with a large amount of neovascularization. Recent publications have reported inguinal neovascularization as the main cause of varicose recurrence [40][41][42] whereas the main cause in older publications was an inadequate initial operation with failure to perform a flush saphenofemoral ligation with ligation and division of all tributaries (so-called extensive crossectomy), leaving a residual refluxing stump. [1][2][3]15,19 Performance of extensive crossectomy by most surgeons for almost 30 years has not reduced the frequency of procedures for varicose recurrence, which remains about 20%, [8][9][10][11]16 but has led to the appearance of a new "source" of varicose recurrence, replacing the residual stump with neovascularization.…”
Section: Discussionmentioning
confidence: 99%